Negotiating an Anglophone identity : a study of the politics of recognition and representation in Cameroon - Konings, Piet (Afrika-Studiecentrum series ;, 2003)
This study of the politics of the politics of belonging captures the widespread disaffection with the sterile rhetoric of nation-building that has characterized much of post-colonial African politics. Until the liberation struggles of the 1990s, dictatorship only paid lip service to democracy with impunity, often by silencing those perceived to threaten national unity. Since then, individuals and groups have reactivated claims to rights and entitlements and nowhere more so than in Cameroon. The book articulates the experiences and predicaments of the country's Anglophone community trapped in a.